2016
DOI: 10.1002/2015rs005883
|View full text |Cite
|
Sign up to set email alerts
|

Large ionospheric disturbances produced by the HAARP HF facility

Abstract: The enormous transmitter power, fully programmable antenna array, and agile frequency generation of the High Frequency Active Auroral Research Program (HAARP) facility in Alaska have allowed the production of unprecedented disturbances in the ionosphere. Using both pencil beams and conical (or twisted) beam transmissions, artificial ionization clouds have been generated near the second, third, fourth, and sixth harmonics of the electron gyrofrequency. The conical beam has been used to sustain these clouds for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 23 publications
(33 reference statements)
4
19
0
Order By: Relevance
“…It shows that Langmuir turbulence due to the HF heating can accelerate part of the ambient photoelectrons to energies above the ionization threshold of the neutral gas, leading to the formation of DAPLs. The present model results are in quantitative agreement with the experiments of Bernhardt et al (2017).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…It shows that Langmuir turbulence due to the HF heating can accelerate part of the ambient photoelectrons to energies above the ionization threshold of the neutral gas, leading to the formation of DAPLs. The present model results are in quantitative agreement with the experiments of Bernhardt et al (2017).…”
supporting
confidence: 90%
“…Eliasson et al () using a complex simulation code demonstrated that the SLT acceleration depended on the presence of electrons with effective temperature in excess of 2–3 times the ambient electron temperature and attributed this to preheating/acceleration at the upper hybrid (UH) region, a few kilometers below. The connection of the DAPL and its relationship to the UH turbulence was later confirmed by subsequent observations by Mishin et al () that indicated that the most efficient DAPL generation takes place when the transmitted frequency is somewhat above multiple harmonics of the electron gyrofrequency and when the HF beam is directed toward the magnetic zenith to generate UH turbulence (Bernhardt et al, ; Sergeev et al, ). Numerical and analytical studies indicated that the efficiency of DAPL was dependent on whether the UH turbulence generated Druyvesteyn‐type heating or high‐energy tails processes that depended on whether the UH frequency was close to an electron cyclotron harmonic or not (Grach, ; Najmi et al, ).…”
Section: Introductionmentioning
confidence: 79%
“…Particularly, it was discovered that HAARP facility provides enough power to produce noticeable (up to 100%) artificial ionospheric ionization. This was found for various pump frequencies regardless of their proximity to harmonics of electron cyclotron frequency, sf ce , s = 2, 3, 4, 6 [Pedersen et al, , 2010Sergeev et al, 2013;Grach et al, 2014;Bernhardt et al, 2016]. In Sergeev et al [2013] and Grach et al [2014] the SEE measurements and sounding of the perturbed ionosphere by short pulses with frequency f DW = f 0 were utilized and the additional evidences of excitation of the artificial ionospheric layers was presented.…”
Section: Introductionmentioning
confidence: 95%
“…Particularly, it was discovered that HAARP facility provides enough power to produce noticeable (up to 100%) artificial ionospheric ionization. This was found for various pump frequencies regardless of their proximity to harmonics of electron cyclotron frequency, sf ce , s = 2, 3, 4, 6 [ Pedersen et al ., , ; Sergeev et al ., ; Grach et al ., ; Bernhardt et al , ]. In Sergeev et al .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, SEE properties were studied with fast pump frequency sweeps mainly for vertical pumping (Carrozzi et al, ; Kotov et al, ), including several experiments for s = 4 with the pump beam inclined to the MZ performed at HAARP for α = 14° (Bernhardt et al, ; Grach et al, ; Sergeev et al, , ) and at “Sura” for α = 14° and 18° (Kotov et al, ). Some results were obtained also in similar experiments for s = 3 and 14° < α < 28° at HAARP (Fu et al, ).…”
Section: Introductionmentioning
confidence: 99%